Qualifying label components for effective biosensing using advanced high-throughput SEIRA methodology. Issue 14 (13th March 2015) - Hornemann, Andrea; Eichert, Diane; Flemig, Sabine; Ulm, Gerhard; Beckhoff, Burkhard
Abstract : The multiplexed SEIRA analysis of antibody-functionalized NP biolabels that can be exploited for specific assay platforms in view of high-performance readout. Abstract : The need for technological progress in bio-diagnostic assays of high complexity requires both fundamental research and constructing efforts on nano-scaled assay recognition elements that can provide unique selectivity and design-enhanced sensitivity features. Nanoparticle induced sensitivity enhancement and its application related to multiplexed capability Surface-Enhanced InfraRed Absorption (SEIRA) assay formats are well suitable for these purposes. The potential of diverse fluorophore–antibody conjugates, being chemisorbed onto low-cost gold nanoparticulate SEIRA substrates, has been explored with respect to their spectral discriminability. These novel biolabels deliver molecular SEIRA fingerprints that have been successfully analyzed by both uni- and multivariate analyzing tools, to discriminate their multiplexing capabilities. We show that this robust spectral encoding via SEIRA fingerprints opens up new opportunities for a fast, reliable and multiplexed high-end screening in biodiagnostics.